(untitled) (Fiep Bulletin - online, 2011)
The inclusion of disabled people is being held, today, as a new paradigm social and educational, aiming at a fairer and more democratic. Despite the initiatives, have a large number of physical and social barriers that prevent effective inclusion process in educational institutions. Therefore, aroused the curiosity to know what is the vision of education professionals and physical therapists on the process of school inclusion. The study was conducted via questionnaires to teachers and principals in 30 schools of Lages / SC, and between CEIM EMEB, physiotherapists and 7 of the municipality. For educational institutions, the major concerns were related to architectural barriers and the preparation of teachers. Since physical therapists believe that their role in the inclusion is through education of the child handling, positioning and adjustments. Some practitioners believe that greater investment should occur in educational policies. But for that to happen, it is necessary to mobilize various sectors of society that are directly or indirectly involved with this issue, walking, thus, the actual school enrollment.